Do emotions predict eating? The role of previous experiences in emotional eating in the lab and in daily life. - Altheimer, Gizem. (Tufts University. Tisch Library., 2019)
Emotional eating (EE) is defined as an increase in eating following negative emotion. Self-reported emotional eating has been associated with physical health concerns. However, experimental and daily diary studies indicate that induced or naturally experienced negative emotions do not reliably lead to increased eating in healthy eaters, not even among self-professed emotional eaters. Recent literature demonstrates that emotional eating may be learned and may depend on associations people have made between specific emotions and eating. Accordingly, in this paper, we propose a set of studies with the overarching goal of determining whether accounting for the variation in people's associations between eating and different discrete emotions would lead to more consistent findings than has been found in the literature thus far. Specifically, in both Study 1 (N = 118) and 2 (N = 111), we asked people to report on their tendency to eat following two discrete emotions (sadness and anxiety) and determined whether and how much they ate when feeling sad or anxious in the lab (Study 1) or in their daily lives (Study 2). Hypotheses, methods, and analysis plans for both studies were preregistered on the Open Science Framework (OSF) platform. We found no support for our hypotheses in either study; self-professed sad- or anxious-eaters did not eat more when induced with these emotions in the lab, or when experiencing these emotions in their daily lives. We discuss why this may have been the case, specifically focusing on the importance of emotion frequency, intensity, timing, and social context.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Psychology.; Advisor: Heather Urry.; Committee: Grace Giles, Robin Kanarek, and Jessica Remedios.; Keyword: Experimental psychology.